Residues : Thinking Through Chemical Environments. - Boudia, Soraya (Nature, society, and culture., 2021)
"Residues offers readers a new approach for conceptualizing the environmental impacts of chemicals production, consumption, disposal, and regulation. Environmental protection regimes tend to be highly segmented according to place, media, substance, and effect; academic scholarship often reflects this same segmented approach. Yet, in chemical substances we encounter phenomena that are at once voluminous and miniscule, singular and ubiquitous, regulated yet unruly. Inspired by recent studies of materiality and infrastructures, we introduce "residual materialism" as a framework for attending to the socio-material properties of chemicals and their world-making powers. Tracking residues through time, space, and understanding helps us see how the past has been built into our present chemical environments and future-oriented regulatory systems, why contaminants seem to always evade control, and why the Anthropocene is as inextricably harnessed to the synthesis of carbon into new molecules as it is driven by carbon's combustion"--